Oceanaut's personal acoustic comfort prediction model and sound environment improvement method in the cabin of a Deep-Sea manned submersible. - Zhu, Mengya; Chen, Dengkai; Wang, Jingluan; Zhang, Xian; Xie, Ning (Ergonomics, 2023)
In this study, a personal acoustic comfort prediction model (PACPM) for exploring the acoustic comfort of oceanauts in a deep-sea manned submersible cabin was proposed, and an oceanauts' task performance model (OTPM) was constructed in this study. Based on oceanauts' comfort and task performance, the change characteristics in six different pure-noise environments (the sound pressure levels of the noise audio are 40 dB (A), 45 dB (A), 50 dB (A), 55 dB (A), 60 dB (A), and 65 dB (A) respectively) were analysed. An effective method for improving acoustic comfort was proposed. According to the analysis, personal comfort at 40 and 45 dB(A) was higher than that at other noise levels. The oceanaut's comfort and task performance of normal-weight people were significantly higher than those of thin people. Meanwhile, a comprehensive consideration of the demographic characteristics and physiological responses can effectively improve the prediction accuracy of the personnel acoustic comfort. Furthermore, the 45 dB (A) pure-noise environment overlaid with 40 dB(A) fast-paced light music effectively improves oceanauts' comfort. Practitioner summary: This study provides a convenient and available method for analysing acoustic comfort in the cabins of deep-sea manned submersibles, including a quantitative prediction model and an effective method for sound environment improvements. These can be used to improve the comfort, task performance, and working efficiency of manned submersibles.